A WUR SNP is associated with European Porcine Reproductive and Respiratory Virus Syndrome resistance and growth performance in pigs. (February 2016) - Abella, Glòria; Pena, Ramona N.; Nogareda, Carmina; Armengol, Ramón; Vidal, Albert; Moradell, Luis; Tarancon, Vicens; Novell, Elena; Estany, Joan; Fraile, Lorenzo
Abstract: Porcine reproductive and respiratory syndrome (PRRS) causes decreased reproductive performance and respiratory problems in pigs. The goals of the current study were 1) to examine whether individual variation applies to infection with PRRSV European strains and 2) to investigate the association of a single nucleotide polymorphism (SNP) WUR10000125 (WUR) at the interferon-inducible guanylate-binding protein 1 gene ( GBP1 ) with average daily gain (ADG) in PRRSV infected and uninfected pigs. The experimental procedure consisted of two trials in which pigs from negative PRRSV farms were infected with a wild-type (n = 80) or vaccinated with an attenuated European PRRS virus strain (n = 40) and then monitored after infection or vaccination. Viral load and ADG were determined for each pig. In a third trial, the ADG for PRRSV-free pigs was monitored. All pigs were genotyped for WUR at the GBP1 gene (AA and AG genotype were defined). Results indicated that there was individual variation in the viral load from pigs challenged with a wild-type or low virulent European PRRSV strain. Secondly, our data showed that WUR SNP was associated to ADG in vaccinated pigs. Thus, ADG in AG pigs was significantly higher than in AA ones after vaccinating with an attenuated PRRSV strain. However, the reverse happened in a PRRSV-free environment where the AA pigs were those that grew faster. Based on these results, there is a scope for selecting pigs according to their responses to PRRS virus infection with European strains and that WUR SNP may play a role in causing PRRSV resistance. Highlights: There is variation in the virus load in challenged pigs with a European PRRSV strain. A WUR SNP is associated with growth rate in pigs challenged with an attenuated European PRRSV strain. The AG pigs perform better than the AA pigs in PRRSV infected animals. The AA pigs show a better performance than the AG pigs in a PRRSV-free environment. Non-viremic pigs will not become a reservoir for an attenuated European PRRSV strain in tonsil.